Checklist of crustaceans (Decapoda and Stomatopoda), collected during the Victor Hensen Costa Rica Expedition (1993/1994) - Vargas C., Rita; Jesse, Sandra; Castro, Mauricio (Revista de Biología Tropical, 1996)
A checklist of the marine crustaceans (Decapoda and Stomatopoda) from the Pacific coost of Costa Rica collected by trawling during the RY Victor Hensen Cruise (1993- 1994) is presented. A total of 117 species were identified. 10 stomatopods and 107 decapods.